2020
DOI: 10.1080/1359866x.2020.1753168
|View full text |Cite
|
Sign up to set email alerts
|

Professional development for intercultural education: learning on the run

Abstract: In many parts of the world, there is a visible increase in the numbers of culturally and linguistically diverse students entering compulsory education. To explore the preparedness of teachers for responding to this diversity, this article reports the findings of an ethnographic study which had a specific focus on Samoan students. In semistructured interviews, teachers of a south-east Queensland primary school described initial challenges they encountered, as well as their opinions about the professional develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Other challenges include those related to international students learning due to education systems, which differ from those in in their home countries. Hence, international students might not be able to perform well because of their failure or inability to meet the requirements of the new educational system in the host culture [39,43]. For instance, Li and Campbell [44] investigated the cultural adjustment of Asian learners in New Zealand, and the study revealed that international students face several challenges varying from their patterns of classroom interaction and lack of academic norms and conventions to inadequate support inside the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…Other challenges include those related to international students learning due to education systems, which differ from those in in their home countries. Hence, international students might not be able to perform well because of their failure or inability to meet the requirements of the new educational system in the host culture [39,43]. For instance, Li and Campbell [44] investigated the cultural adjustment of Asian learners in New Zealand, and the study revealed that international students face several challenges varying from their patterns of classroom interaction and lack of academic norms and conventions to inadequate support inside the classroom.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they consider that this relationship produces cultural enrichment for both groups. In cases where problems of intercultural coexistence arise, these are solved by teaching values and introducing cultural references in all subjects of the curriculum [54][55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Intercultural competence is one of the goals of multicultural education. Students are expected to have the competence to interact with people of different cultures while respecting cultural differences (Jun, 2016;Tualaulelei, 2020). According to Byram et al (2002), there are five dimensions of intercultural competence, namely intercultural attitudes, knowledge, skills of interpreting and relating, skills of discovery and interaction, and critical cultural awareness.…”
Section: A Brief Highlights Of Intercultural Sensitivitymentioning
confidence: 99%